Dielectric and piezoelectric properties of B2O3 and SnO2 doped barium titanate ceramics - Tawichai N. (2014)
Boron oxide doped barium stannate titanate ceramics were prepared by a solid-state reaction method. Properties of the ceramics were investigated. The experimental results showed that most properties of the ceramics depend on the sintering temperature. The higher relative permittivity of 13887 with tanδ ∼0.034 at 34 °C was observed for the samples sintered at 1350 °C. Piezoelectric coefficient (d33) of the samples was found to be in the range of 90-115 pC/N. However, the optimum d33 coefficient was observed for the sample sintered at 1250 °C. © 2008 Trans Tech Publications, Switzerland.